2022
DOI: 10.3389/fpubh.2022.900899
|View full text |Cite
|
Sign up to set email alerts
|

Experience of using a smartphone WeChat applet for dental anxiety assessment and preoperative evaluation: A nationwide multicenter study

Abstract: IntroductionDental anxiety is a multivariate phenomenon that regularly occurs during a dental procedure. Although it may lead to patients' safety concerns and adverse events in routine treatment, it is often ignored. The purpose of this research is to develop a novel WeChat Applet for dental anxiety (WADA) with the following features and aims: (1) to help patients with dental anxiety management; (2) provide patient with a physical status self-evaluation; and(3) provide a platform for online assessment and tele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The studies belonged to four categories: randomized controlled clinical trials [41][42][43][44][45][46][47][48][49][50][51], cross-sectional studies [52], before-after (pre-post) studies with no control group [53], and observational studies [54][55][56][57][58][59][60]. Table S3 (Supplementary Materials) shows the studies excluded from this review and the reasons for exclusion [30][31][32][33][34][35][36][37][38][39][40].…”
Section: Resultsmentioning
confidence: 99%
“…The studies belonged to four categories: randomized controlled clinical trials [41][42][43][44][45][46][47][48][49][50][51], cross-sectional studies [52], before-after (pre-post) studies with no control group [53], and observational studies [54][55][56][57][58][59][60]. Table S3 (Supplementary Materials) shows the studies excluded from this review and the reasons for exclusion [30][31][32][33][34][35][36][37][38][39][40].…”
Section: Resultsmentioning
confidence: 99%
“…The survey also indicates high user satisfaction with the pharmaceutical care provided by XMG. According to the report, multitudinous APPs only involved dozens or hundreds of patients for the comparative study; their number of users was not shown ( Huang et al, 2022 ; Liu et al, 2022 ; Sun et al, 2022 ). The “Cloud Pharmacy Care” platform acquired 1,432 views and completed 39 counseling cases in 2 months, was much less than the XMG ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The medical landscape has witnessed the proliferation of more than 318,000 medical apps designed to aid in disease diagnosis and management ( Huang et al, 2022 ). One such notable example is the novel shared WeChat app developed by Huang et al, specifically tailored to address dental anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…After the dental surgery was finished, the patient was transferred to a recovery area. Patients were followed up with by an original developed smartphone-based applet WeChat Applet for dental anxiety the next day to record any AEs and intelligent feedback (eFigure 1, Supplemental Digital Content 4, http://links.lww.com/JS9/A652 ) 27 .…”
Section: Methodsmentioning
confidence: 99%